High-Performance Work System & Employee Performance in Public Sector: Testing the Mediating Effect of Job Engagement - Saba Feroz , Qureshi; Khawaja Asif , Tasneem (European Scientific Journal, ESJ, 2021)
The purpose of this paper is to investigate the impact of high-performance work systems on employee performance mediated by job engagement of the employees working in the public sector organization. The paper attempts to explain how high-performance work systems influence the employees and motivate them to perform in the organization. The study goals to deliver the understanding of high-performance work systems that influences job engagement which in turn significantly affects employee performance. To test the study’s hypotheses, we collected data from a field study of 500 employees working in 25 public sector banks. Our results show that a high-performance work system is significantly related to employee performance and this relationship is mediated by job engagement. This shows that employees who are given improved high-performance work systems showed high job engagement along with high employee performances regardless of their gender and other diversity. Perspectives related to high-performance work systems pose a positive outcome on the employee performance are considered dominant in the current investigation.